2018
DOI: 10.1001/jamanetworkopen.2018.0382
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use Among American Indian Youths on Reservations Compared With a National Sample of US Adolescents

Abstract: Key Points Question How do substance use rates among American Indian youths compare with rates among national US adolescents? Findings Lifetime and last-30-day substance use rates and relative risk were significantly higher for nearly all substances among American Indian youths. Meaning Early prevention and culturally sensitive interventions are needed for this population in addition to careful screening by medical staff for sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
87
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 46 publications
6
87
0
Order By: Relevance
“…The prevalence and manifestation of substance abuse disorders is arguably the most well‐researched area in contemporary AI/AN research. Substance and drug use among tribal members continues to pose a significant problem, as the rates of substance use are significantly higher in AI/AN youth, with 23–56% of AI/AN youth between the eighth and twelfth grades report having been drunk in the last 30 days, compared to 8–45% in national U.S. adolescents (Swaim & Stanley, 2018). Research conducted by Stanley and colleagues (2014) also revealed that AI/AN youth had higher rates of substance use across all drug categories with the exception of amphetamines and tranquilizers.…”
Section: Ai/an Youth Mental Health and Delinquencymentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence and manifestation of substance abuse disorders is arguably the most well‐researched area in contemporary AI/AN research. Substance and drug use among tribal members continues to pose a significant problem, as the rates of substance use are significantly higher in AI/AN youth, with 23–56% of AI/AN youth between the eighth and twelfth grades report having been drunk in the last 30 days, compared to 8–45% in national U.S. adolescents (Swaim & Stanley, 2018). Research conducted by Stanley and colleagues (2014) also revealed that AI/AN youth had higher rates of substance use across all drug categories with the exception of amphetamines and tranquilizers.…”
Section: Ai/an Youth Mental Health and Delinquencymentioning
confidence: 99%
“…For instance, AI/AN youth have the highest rates of fetal alcohol syndrome, a serious birth defect caused by repeated exposure to alcohol in utero which is associated with numerous intellectual and neurodevelopmental disabilities, with rates nearly double that of the average across all ethnic groups in the United States (Fox et al., 2015). Notably regarding mental health disparities, AI/AN youth aged 15–24 have the highest suicide rate among all racial and ethnic groups in the United States (Curtin & Hedegaard, 2019), as well as the highest rates of alcohol and drug addiction (Swaim & Stanley, 2018; U.S Department of Health and Human Services, 2018). In general, AI/AN youth living on a reservation also appear to have worse outcomes than their urban‐dwelling AI/AN counterparts (Freedenthal & Stiffman, 2004), though research comparing the two is limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By continuing to expand on the understanding of protective factors and incorporating urban AI/AN youth into studies and research, public health interventions for AI/AN youth can be improved and contribute to lifting the overall health and well-being of all AI/AN people. Prevention efforts that do not consider cultural and contextual factors may have lower chances of success (Swaim & Stanley, 2018). By understanding institutionalized racism and bias within the education system and focusing on protective factors, communities can move forward towards a positive, more inclusive future.…”
Section: Discussionmentioning
confidence: 99%
“…While very few entrepreneurship education interventions have been implemented on Native American reservations and none until now have been rigorously evaluated, entrepreneurship education interventions appear particularly promising for Native American (NA) youth living on reservations for two reasons: (1) Strengths-based approaches are highly congruent with Native views of ways to promote health and well-being [22][23][24][25][26][27][28][29][30], and (2) NA adolescents face some of the worst social, economic, health, and education risks of any racial or ethnic group in the U.S. [31][32][33][34]. Increasing recognition that social determinants, most notably poverty, and health status are inextricably linked supports the need for rigorous research on positive youth development approaches addressing both [1][2][3].…”
Section: Evidence From Past Youth Entrepreneurship Trialsmentioning
confidence: 99%